Panama as a cruise ship resupply hub - Barrios Samudio. Larissa Liz; Burgess, Alexis Jahil; Ramudhin, Amar, 1961-; Ratliff H., Donald, 1943- (Panamá : Universidad Tecnológica de Panamá, 2011)
The "Panamas as a Cruise Ship Resupply Hub" project examines the potential of Panama for resupplying cruise ships focusing in food and beverages through an assessment of the current logistics involved for replenishing cruise ships in the Colon 2000 homeport and other regional homeports. Currently, there are two cruise ships depart from Panama: Grandeur of the Seas of Royal Caribbean and Ocean Dream of Pullmantur. The purpose of this research is to analyze the supply chain strategy that cruise lines adopt as well as identifying which local and imported products could be efficiently supplied from the country, and outlining what will be required in infrastructure, equipment, and other services for resupplying cruises in Panama and other regional homeports. Panama has several advantages that allow the country to gain entry into the cruise food provisioning industry. Some unique features that give Panama the opportunity to compete in this market are the country's strategic geographic position and logistics assets that allow forming strong connections with major ports of the region, and providing connectivity to several overseas markets. The supply chain involved for resupplying cruise ships can be described as follows: it starts in the farmlands or manufacturer, and then it gets to a supplier or a ship chandler. The supplier or the ship chandler can ship the goods directly to the cruise ship or to a Cruise Distribution Center, and in the end this distribution center will consolidate and dispatch the cargo to their respective homeports for resupplying the cruise ships. The cost of resupplying cruise ships in Panama with imported containers from Miami is approximately $10 million dollars per cruise season; while shipping directly the sources to Panama has a total cost around $9 million dollars per season. Our proposed network for consolidating and redistributing cargo in Panama rather than in Miami could save up to $6 million dollars per cruise season. The main points for developing a distribution center for cruise food resupply in Panama are: sourcing directly to Panama, a ship chandler in charge for consolidating and distributing the goods and providing high quality of products.
Introduction. -- Chapter I. Project setting. -- Chapter II. Current situation. -- Chapter III. Proposed network configuration. -- Chapter IV. Analysis. -- Conclusions. -- Recommendations. -- Further research. -- Glossary. -- References.
Tesis (
Incluye referencias, página 45-46.
MCICS
Depósito UTP.
Keywords: Transporte acuático; Cruceros; Embarque de mercancias; Abastecimiento de alimentos; Logística en los negocios; Distribución física de mercancías; Ingeniería industrial; Tesis y disertaciones académicas; Panamá; Maestría en Ciencias en Ingeniería de la Cadena de Suministros